Antibacterial and Carbohydrate Digestive Enzyme Inhibitory Effects of Native Plants Used for Medicinal and Culinary Purposes in Cyprus - Christou, Atalanti; Stavrou, Constantina; Michael, Christodoulos; Botsaris, George; Goulas, Vlasios (My University, 2024)
Natural products are an inexhaustive reservoir of bioactive compounds with diverse effects protecting human health as components of nutrition and as active substances of drugs. The objective of the present study was to evaluate the bactericidal and carbohydrate digestive enzyme inhibitory activity of twelve native plants from Cyprus, that are consumed for medicinal and/ or culinary purposes. Each plant was sequentially extracted with solvents of increasing polarity, from non-polar to polar solvents. At first, the total phenolic (TPC) and flavonoid (TFC) content of the extracts were determined. The bactericidal potential of plant extracts was tested against six bacteria using the broth microdilution method. Furthermore, their inhibitory effects on digestive enzymes, namely α-glucosidase and α-amylase, were also determined. Results demonstrated a substantial diversity in TPC (2.3-483.5 mg gallic acid equivalent g−1) and TFC (4.1-394.6 mg catechin equivalent g−1) of the plant extracts; a great impact of solvent was found. Furthermore, potent antibacterial activity (minimum bactericidal concentration ≤ 500 µg ml−1) of capper, mountain oregano, rosemary, silver thistle, and vine leaf extracts against Gram-positive bacteria was determined. Regarding carbohydrate digestive enzyme inhibitory effects, the inhibition of α-glucosidase enzyme is higher than 80%, when rosemary, silver thistle, and vine leaf extracts are used at a concentration of 500 µg g−1. Overall, the present study describes the antibacterial and inhibitory effect against carbohydrate digestive enzymes of unstudied plant species or known plants from the unexplored island of Cyprus. It provides valuable data for the nutraceutical value of native edible plants as well as assesses these plants as potential sources of antibacterial and carbohydrate digestive enzyme inhibitory agents for drug discovery.
Keywords: α-glucosidase; α-amylase; Antidiabetic activity; Antimicrobial activity; Bioactivity; Extracts; Flavonoids; Phenolics